Pop-up Card to Teach Regular and Irregular Past Verbs - A, Rizka D. A.; Wahyuni, Sri; Priyatmojo, Arif Suryo (ELT Forum: Journal of English Language Teaching, 2018)
This paper is based on an experimental research aiming to explain to what extent the achievement of the students who were taught by using pop-up card differs from those who were taught by using regular teaching media used by the teacher in attaining regular and irregular past verbs and to describe how effective pop-up card is to teach regular and irregular past verbs. The subject of the study was the students of VIII C, as the control group, and VIII D, as the experimental group, of one of junior high schools in Semarang in the academic year of 2016/2017, consisting of 60 students, chosen by using convenience sampling. This study used pretest-posttest control group design as a part of quasi-experimental design. The experimental group was taught regular and irregular past verbs by using pop-up cards and the control group was taught by using regular teaching media used by the teacher. T-test of the data showed that tvalue is higher than ttable (2.494 > 1.67). It can be concluded that there was a significant difference between the achievement of the students who were taught by using pop-up card and those who are taught by using regular teaching media used by the teacher.